1976
DOI: 10.1093/bja/48.3.243
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Thoracic Extradural Analgesia on Pulmonary Gas Distribution, Functional Residual Capacity and Airway Closure

Abstract: Pulmonary gas distribution, functional residual capacity (FRC), closing capacity (CC), arterial oxygen tension (PaO2) and alveolar-arterial oxygen tension gradient (PAO2-PAO2) were measured in seven subjects before and after the induction of extradural analgesia for routine surgery. It was found that pulmonary gas distribution was within normal limits throughout the study, although there were two patients in whom airway closure occurred consistently within the tidal volume. In both cases this was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
2

Year Published

1980
1980
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 13 publications
3
10
0
2
Order By: Relevance
“…[19] In contrast, others have not found that TEA has any influence on spirometry or lung dynamics. [20] In our study, we found better spirometric values in patients who received TEA, probably due to better analgesia as demonstrated by lower VAS values both at rest and coughing. We also used low concentration (0.125%) of bupivacaine which is unlikely to produce motor paralysis.…”
Section: Discussionsupporting
confidence: 60%
“…[19] In contrast, others have not found that TEA has any influence on spirometry or lung dynamics. [20] In our study, we found better spirometric values in patients who received TEA, probably due to better analgesia as demonstrated by lower VAS values both at rest and coughing. We also used low concentration (0.125%) of bupivacaine which is unlikely to produce motor paralysis.…”
Section: Discussionsupporting
confidence: 60%
“…Mismatching of ventilation and perfusion in the lungs is accompanied by impairment of pulmonary gas exchange [3,4]. Epidural anaesthesia, on the other hand, does not appear to influence FRC or airway closure and has little effect on the ventilation/perfusion match (V A /Q ) [5,6]. However, epidural anaesthesia causes alterations of chest wall motion that may affect regional lung volume and ventilation [7,8].…”
mentioning
confidence: 99%
“…This is the first study in children examining the impact of a neuroaxial blockade on FRC. Only studies performed in adults are available to compare our findings on the effect of epidural anaesthesia on FRC [17][18][19][20][21]. While some of the adult studies found no effect of lumbar or thoracic epidural anaesthesia [18][19][20], others showed a decrease [21] or an increase in FRC [17].…”
Section: Discussionmentioning
confidence: 86%